A Survey of Image Encryption Algorithms - Kumari, Manju; Gupta, Shailender; Sardana, Pranshul (3D research, 2017)
Security of data/images is one of the crucial aspects in the gigantic and still expanding domain of digital transfer. Encryption of images is one of the well known mechanisms to preserve confidentiality of images over a reliable unrestricted public media. This medium is vulnerable to attacks and hence efficient encryption algorithms are necessity for secure data transfer. Various techniques have been proposed in literature till date, each have an edge over the other, to catch-up to the ever growing need of security. This paper is an effort to compare the most popular techniques available on the basis of various performance metrics like differential, statistical and quantitative attacks analysis. To measure the efficacy, all the modern and grown-up techniques are implemented in MATLAB-2015. The results show that the chaotic schemes used in the study provide highly scrambled encrypted images having uniform histogram distribution. In addition, the encrypted images provided very less degree of correlation coefficient values in horizontal, vertical and diagonal directions, proving their resistance against statistical attacks. In addition, these schemes are able to resist differential attacks as these showed a high sensitivity for the initial conditions, i.e. pixel and key values. Finally, the schemes provide a large key spacing, hence can resist the brute force attacks, and provided a very less computational time for image encryption/decryption in comparison to other schemes available in literature.